2019
DOI: 10.1016/j.scitotenv.2018.12.353
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal gene transfer and shifts in linked bacterial community composition are associated with maintenance of antibiotic resistance genes during food waste composting

Abstract: This is a repository copy of Horizontal gene transfer and shifts in linked bacterial community composition are associated with maintenance of antibiotic resistance genes during food waste composting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(19 citation statements)
references
References 56 publications
0
18
0
1
Order By: Relevance
“…Han et al reported that community composition was the main factor driving changes in ARG abundance in a mariculture sediment 59 . Liao et al found that shifts in bacterial community composition were associated with the maintenance of ARGs in food waste composting 60 . Thus, further work is needed to better understand how bacterial community shift drive ARG alteration in the food samples.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al reported that community composition was the main factor driving changes in ARG abundance in a mariculture sediment 59 . Liao et al found that shifts in bacterial community composition were associated with the maintenance of ARGs in food waste composting 60 . Thus, further work is needed to better understand how bacterial community shift drive ARG alteration in the food samples.…”
Section: Discussionmentioning
confidence: 99%
“…Procrustes analysis for samples in the cattle study were performed by treatment group, and by time within each treatment group. Procrustes analysis has been previously applied in a number of studies including the characterization of resistomes and colocalization of resistant determinants and MGEs ( Noyes et al, 2016 ; Wu et al, 2017 , 2018 ; Zhu et al, 2017 ; Liao et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Spent coffee grounds (SCGs) are generated from approximately 91 wt% of the whole coffee bean in coffee processing [2]. SCGs are buried in landfills, causing environmental pollution such as soil, water and air pollution and the emission of greenhouse gases [3]. In addition, disposable coffee cups made of plastic have been associated with these forms of pollution [4].…”
Section: Introductionmentioning
confidence: 99%